BUILDING KINSHIP NEGOTIATIONS: DEFINITION OF SOCIAL PROTECTION FOR CHILDREN OF INDONESIAN MIGRANT WORKERS - Kristina, Anita; Jumali , Muhamad Abdul (Universitas Airlangga, 2025)
This study examines how children of Indonesian migrant workers construct their own social protection and navigate relationships within extended families. This study explores how social protection emerges through kinship negotiations based on children’s perceptions. When parents migrate for work, children face challenges and rely on extended family members for care. Using a qualitative phenomenological approach, this study identifies patterns of kinship negotiations that shape social protection. Data were collected through in-depth interviews with children aged 7–15 in East Katol Village, Madura, Indonesia, who live with extended families due to parental migration. Findings reveal that children perceive social protection as central to familial relationships, engaging in negotiations embedded in kinship traditions. They extend protection beyond biological relatives, including non-relatives considered